Political Conflict Over the Construction of a Tower in Menduran Village, Brati District, Grobogan Regency - Winantar Wijayanti, Susi; Syamsudin, Nur (Social Sciences and Humanities Reviews, 2025)
Background: Conflicts often arise in village development when communication among stakeholders is lacking transparency and community participation is limited. This situation can hinder the achievement of sustainable and inclusive development. Aims: This study aims to analyze the dynamics of conflict in the construction of a telecommunication tower in Tegowanu Kulon Village, identify the root causes and forms of conflict, and explore conflict resolution efforts undertaken by the relevant parties. Methods: This study used a qualitative approach with a case study design. Data collection techniques included interviews, observation, and documentation. Data analysis was conducted using Braun and Clarke's thematic method through the stages of familiarization, coding, theme identification, review, definition, and reporting. Results: The results of the study indicate that conflicts arise due to a lack of socialization, differing interests, and community concerns about the negative impacts of tower construction. The forms of conflict that emerge include protests, rejection, and the submission of petitions. Conflict resolution is carried out through mediation involving the village and district governments, using peace-making, peace-keeping, and peace-building strategies. Conclusion: This study emphasizes the importance of transparent communication, active community participation, and trust-building among parties in conflict resolution. Effective conflict management at the village level not only stops disputes but also transforms social relations toward more inclusive and sustainable development.